Unravelling the immune signature of Plasmodium falciparum transmission-reducing immunity - Will J. R. Stone (Nature Portfolio, 2018)
Naturally acquired antibodies may inhibit Plasmodium survival in mosquitoes, alter malaria transmission dynamics, and form the basis for transmission-blocking vaccines. Here, using sera from malaria-exposed individuals, Stone et al. reveal novel antibody correlates of transmission-reducing activity.